Kinerja Bank Pasca Konversi Menjadi Bank Syariah: Lebih Baik Atau Lebih Buruk? - Sari, Nurma; Hasnanti Putri, Windi; Umuri, Khairil (JIMEBIS: Scientific Journal of Students Islamic Economics and Business, 2022)
This study aims to compare the quality of service and loyalty in Bank before and after to find out the impact of service quality on customer loyalty before and after becoming Bank Syariah. The method used in this research is quantitative. The population in this study up to 60,000 customers. The samples obtained were 100 customers by using Slovin formula with sample technique that is purposive sampling. This research used questionnaire as its instrument. Hypothesis testing in this study consisted of Paired sample t-Test and Structural Equation Model (SEM) Test. Paired sample t-test is to compare service quality and loyalty at Bank before and after conversion. Test SEM used to find out the influence of service quality to loyalty before and after conversion. The result of Paired sample t-test showed that service quality and customer loyalty have better effect than before conversion. And the result of Structural Equation Model (SEM) with maximum likelihood estimation (MLE) method showed that service quality influence loyalty before and after becoming Bank Syariah conversion with significance value of p <0,001.